THE SECURITY ASPECTS OF PRISONS - Zahars, Vitolds; Stivrenieks, Māris (Administrative and Criminal Justice, 2015)
Nowadays the prisons management and process control are based not only to physical security of prisons (premises, buildings, engineering equipment and technological equipment), but more to dynamic security (positive relationship between prison staff and inmates, based to rigidity and equity). The article reflects the results of the research about custodial sentence enforcement aspects of security in Latvian prisons. In this research are highlighted specificities of custodial sentence enforcement aspects of security in imprisonment places from point of view of rights of the custodial sentence enforcement law and practice. In this research are identified issues of the problem and suggested possible solutions. Within the framework of the research the norms of the Sentence Execution Code of Latvia, Prisons Administration Act and Regulations No.423 of the Cabinet of Ministers of May 30, 2006 – Internal rules of Penitentiary institutions, have been analyzed based on the safety aspects of the prison and its compliance with the requirements of generally accepted human rights, the Council of Europe and international norms and standards. Within the research the scientific literature and viewpoints from legal experts have been collected and analyzed. The aim of the research is to show, that the safety aspects of the prisons are insufficiently and inaccurately regulated and requires a deeper analysis. On the bases of this research were developed series of recommendations for prison staff to comply with the safety aspects of prisons as well as the necessity to make amendments in norms of the Sentence Execution Code of Latvia, Prisons Administration Act and Regulations No.423 of the Cabinet of Ministers of May 30, 2006 – Internal rules of Penitentiary institutions.